KAJIAN PEMANFAATAN MEDIA PEMBELAJARAN LEAFLET TERHADAP PENINGKATAN HASIL BELAJAR PESERTA DIDIK - Widia Wahyuni; Rahmadhani Fitri; Rahmawati Darussyamsu (Universitas Islam Negeri Sumatera Utara, 2022)
Learning media is an important element in the learning process. Innovative learning certainly greatly affects students interest and motivation in learning. One of the learning media that can be used is leaflet. Leaflet is printed media in the form of sheets (folded), equipped with picture and contains a summary of material related to a subject. This research is a research that aims to examine the results of the analysis of the use of leaflet in the learning process from the result of various tests that have been carried out previosly. This research is also used to find out how the influence of the use of the leaflet media on student learning outcomes. This research was conducted using a meta-analysis method, riviewing library sources such as articles, theses and related journals. Based on the results of the analysis of the research that has been done by the researcher, it shows that this leaflet-based learning media has a high effect on increasing students understanding and activity in learning. The increase in student learning activities also has an impact outcomes in the learning process.